OSTEOARTHRITIS DISEASE AND ITS REHABILITATION - Safarov Abdirashid Juraevich; Akhmedova Durdona Shakirovna (Western European Studies, 2024)
To prevent and detect osteoarthritis of the knee joint among the population of Uzbekistan, different degrees of osteoarthritis were determined in 120 patients during 2022- 2023. The patients were aged between 28 and 75, most of them were women (on average 80%) and we studied the origin of the disease - age, sex, hereditary diseases, concomitant diseases, lifestyle, weight, and harmful habits and analyzed based on several principles. and evaluated. We put the obtained data in tables and diagrams for easy analysis. From the obtained data, it became clear that the number of patients suffering from osteoarthritis is much higher than that of men, and the reason for this is that our women do little or no physical education, which leads to an increase in overweight people. Failure to treat osteoarthritis in time has been found to have a high rate of early disability
Keywords: Women; nutrition; physical activity; bad habits